Archival Data in Micro-Organizational Research: A Toolkit for Moving to a Broader Set of Topics. (April 2018) - Barnes, Christopher M.; Dang, Carolyn T.; Leavitt, Keith; Guarana, Cristiano L.; Uhlmann, Eric L.
Compared to macro-organizational researchers, micro-organizational researchers have generally eschewed archival sources of data as a means of advancing knowledge. The goal of this paper is to discuss emerging opportunities to use archival research for the purposes of advancing and testing theory in micro-organizational research. We discuss eight specific strengths common to archival micro-organizational research and how they differ from other traditional methods. We further discuss limitations of archival research, as well as strategies for mitigating these limitations. Taken together, we provide a toolkit to encourage micro-organizational researchers to capitalize on archival data.